GROWTH AND ASSESSMENT OF NIOSOMAL FORMULATIONS - Shweta Swamy, Dr.D.Nagendra Kumar (EPRA International Journal of Research and Development (IJRD), 2024)
The invasive fungal infection requires a long treatment schedule; however, treatment becomes more cumbersome due to the development of resistance. Most anti-fungal moieties show systemic toxicity upon oral administration. Eberconazole (EBZ) is a BCS class II drug that has poor solubility and high permeability. Niosomes are vesicular carriers that can entrap both hydrophilic and lipophilic drugs. The formulation has shown 86 ± 0.85% entrapment efficiency while noisome appeared ring-like structure during its microscopic evaluation. Further evaluations of its in vitro and in vivo release studies will be performed in the future for its efficacy and anti-fungal activity.